Flat-Headed Bats (Mammalia, Tylonycteris) From the Philippine Islands - Heaney, Lawrence R.; Alcala, Angel C. (Silliman Journal, 2024)
Tylonycteris robustula is reported for the first time from the Philippines: specimens are available from Calauit and Luzon. Records of Tylonycteris robustula are from Calauit, Culion, Palawan, Luzon and Mindanao; other reports are probably erroneous. These records bring the number of species of the bat family Vespertilionidae in the Philippines to 21. No species are endemic, and most are widespread in the tropical portions of the Oriental and Australian zoogeographic regions. A few are shared only with the continent and continental shelf islands of Asia.